Lessons Learned from Community-Led Recruitment of Immigrants and Refugee Participants for a Randomized, Community-Based Participatory Research Study - Hanza, Marcelo M.; Goodson, Miriam; Osman, Ahmed; Capetillo, Maria D. Porraz; Hared, Abdullah; Nigon, Julie A.; Meiers, Sonja J.; Weis, Jennifer A.; Wieland, Mark L.; Sia, Irene G. (Journal of immigrant and minority health, 2016)
Ethnic minorities remain underrepresented in clinical trials despite efforts to increase their enrollment. Although community-based participatory research (CBPR) approaches have been effective for conducting research studies in minority and socially disadvantaged populations, protocols for CBPR recruitment design and implementation among immigrants and refugees have not been well described. We used a community-led and community-implemented CBPR strategy for recruiting 45 Hispanic, Somali, and Sudanese families (160 individuals) to participate in a large, randomized, community-based trial aimed at evaluating a physical activity and nutrition intervention. We achieved 97.7 % of our recruitment goal for families and 94.4 % for individuals. Use of a CBPR approach is an effective strategy for recruiting immigrant and refugee participants for clinical trials. We believe the lessons we learned during the process of participatory recruitment design and implementation will be helpful for others working with these populations.